Shell growth of the golden mussel, Limnoperna fortunei (Dunker, 1857) (Mytilidae), in the Río de la Plata, Argentina - Maroñas, Miriam Edith (2003)
The golden mussel, Limnoperna fortunei, is an invasive freshwater bivalve. Since its introduction to Argentina, it had caused damage to the native fauna as well as economic damage to industries of the region. Here, we describe the growth of L. fortunei in a natural temperate environment in Argentina. Age was estimated according to the modal progression method. The constants in the von Bertalanffy growth model were adjusted by an iterative algorithm. Three annual cohorts had similar growth rates. The estimated t0 for each cohort showed a temporary displacement in relation to the spawning period.